OPTIMIZATION OF INJECTION MACHINE PARAMETERS ON HIGH TENSILE STRENGTH OF POLYPROPYLENE/FIBREGLASS - Ali, M.A.M.; Idayu, N.; Salleh, M.S.; Sivaraos, S.; Yamaguchi, M. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
The objective of this study is to investigate the optimum process parameters on the high tensile strength of mechanical properties in the injection machine process. The injection machine parameters selected are melt temperature, holding pressure, injection time and cooling time. Taguchi and ANOVA method were performed for design the experimental matrix and to find the most significant of the parameters. PP having 20% of fibreglass was employed. Injection machine Arburg 420C 800-250 having 80 ton of clamping force has been used to moulded the dumbbell shape test sample according to ASTM D638 standard. The tensile test was performed using the universal testing machine. The result shows that the most significant factors that affected the tensile strength are cooling time, followed by injection time, holding pressure and melt temperature. Cooling time contributes 61.13%, meanwhile, injection time, holding pressure and melt temperature contribute each of them 20.15%, 13.41% and 5.32% respectively. Optimization of cooling time at 10 s, injection time at 0.5 s, holding pressure at 350 MPa and melting temperature at 205 °C shows the highest tensile strength 20.9243 MPa and desirability value is 1. Thus, by using the Taguchi optimization method the optimize parameters of injection machine parameters can be determined with the achievement of the highest tensile strength.